Stress Free Living - Powell, Trevor , Dr. (London Dorling Kindersley, 2000)
A practical guide which aims to show you how to recognise the danger signals of stress by suggesting methods to manage your life in a positive life-affirming way. Action plans outline strategies for becoming more assertive, improving your relationships and freeing yourself from stress.
Include Index and Illustration
Keywords: Stress management -- Relaxation -- Self-actualization (Psychology)